Furniture names are included in English and Uzbek articles - Dildora Urokova Ibragimovna (NEW SCIENTIFIC PERSPECTIVES AT THE INTERSECTION OF LANGUAGE, CULTURE, AND TECHNOLOGY, 2026)
This thesis explores the integration and adaptation of furniture names within English and Uzbek linguistic contexts, focusing on how terminology from these languages appears in articles, media, and scholarly works. By examining bilingual articles that incorporate furniture-related vocabulary, the study highlights linguistic borrowing, translation strategies, and cultural influences on nomenclature. Furniture terms, such as "chair" (English) and "stul" (Uzbek), often reflect historical trade routes, colonial impacts, and modern globalization, leading to hybrid forms in multilingual content [1]. The analysis extends to semantic shifts, where English terms like "sofa" may be transliterated as "divan" in Uzbek contexts, preserving etymological roots from Persian influences while adapting to contemporary usage [2]. Through a comparative lens, this work investigates how such integrations affect readability, cultural representation, and language policy in bilingual publications. The thesis draws on a corpus of over 500 articles from English-Uzbek sources, revealing patterns in code-switching and lexical assimilation. Findings suggest that furniture nomenclature serves as a microcosm for broader linguistic convergence in Central Asia, particularly in Uzbekistan's evolving media landscape [3]. This research contributes to applied linguistics by proposing guidelines for translators and educators to enhance cross-cultural communication in furniture-related discourse.